1992
DOI: 10.2337/diab.41.10.1355
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Glutamic Acid Decarboxylase (Representing the Single Isoform Expressed in Human Islets) Detects IDDM-Associated 64,000-Mr Autoantibodies

Abstract: GAD is an autoantigen in IDDM. Molecular cloning and specific antibodies allowed us to demonstrate that only the lower M r GAD64 isoform is expressed in human islets, in contrast to human brain, rat islets, and rat brain, all of which express both GAD64 and GAD67. Expression of the human islet GAD64 isoform in COS-7 and BHK cells resulted in an enzymatically active rGAD64, which is immunoreactive with diabetic sera comparable with that of the islet 64,000-Af r autoantigen. Immunoprecipitation analyses showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 20 publications
2
32
0
Order By: Relevance
“…The availability of cDNA sequences for human islet [7] and brain [8] GAD65 enabled their amino acid sequence comparison and showed these to be identical. The present study supports previous demonstrations that the GAD65 mRNA [7] codes for the 64K antigen [12,21,37]. The results of this study also confirm other studies [12,18,20] but fail to support investigations showing that IDDM sera have significant reactivity to GAD67 [13] or GAD67 peptide fragments [16].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The availability of cDNA sequences for human islet [7] and brain [8] GAD65 enabled their amino acid sequence comparison and showed these to be identical. The present study supports previous demonstrations that the GAD65 mRNA [7] codes for the 64K antigen [12,21,37]. The results of this study also confirm other studies [12,18,20] but fail to support investigations showing that IDDM sera have significant reactivity to GAD67 [13] or GAD67 peptide fragments [16].…”
Section: Discussionsupporting
confidence: 70%
“…The use of different assay systems and species-specific GAD65 and GAD67 may explain the lower frequency of GAD67 antibodies in these compared to previous reports [13,16]. We now report the use of GAD65 [7,21] and GAD67 [10] cDNA to synthesize by in vitro translation and transcription specific radioactive ligands used in a radioimmunoassay of GAD65 and GAD67 antibodies and the use of the ROC plot [22][23][24][25] to determine the diagnostic accuracy of the GAD antibody test. addition of translation mixture and 5 gCi 35S-methionine (Amersham Int., Amersham, Bucks., UK; > 1000 Ci/mmol) and incubation for 90 rain at 30~ Translation products were analysed by SDS-PAGE and autoradiography to demonstrate the presence of M r 65,000 and Mr 67,000 components for GAD56 and GAD67 (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Initial reports indicated that GAD was predominantly observed in beta cells and primarily stored within the SMLVs (1.9). However, more recent studies suggest a strong degree of species and islet endocrine cell variation in GAD expression (20, 21) Specifically, rat islets were shown to contain both isoforms of GAD, whereas human islets expressed only GAD 65, and GAD expression within islets was not limited to the beta cells (20,21). Recombinant produced GADs have been used to detect GAD 65 and GAD 67 autoantibodies in persons with or at risk for IDD (21,22).…”
Section: -Kd/gad Autoantigenmentioning
confidence: 99%
“…However, more recent studies suggest a strong degree of species and islet endocrine cell variation in GAD expression (20, 21) Specifically, rat islets were shown to contain both isoforms of GAD, whereas human islets expressed only GAD 65, and GAD expression within islets was not limited to the beta cells (20,21). Recombinant produced GADs have been used to detect GAD 65 and GAD 67 autoantibodies in persons with or at risk for IDD (21,22). One study (22) reported that the anti-64-kD response was primarily composed of an anti-GAD 65 activity, that multiple autoantibody epitopes were present within GAD (although none were identified within the NH2-terminal 200 amino acids), that a region of GAD has a homologous protein sequence with the P2-C protein of coxsackie B4 virus, and that some forms ofneuropathy in IDD may be associated with anti-GAD immunity.…”
Section: -Kd/gad Autoantigenmentioning
confidence: 99%